THE VALUE OF EDUCATION ON FILM SOKOLA RIMBA - Mardianto, Mardianto; Aslami, M. Rizqi (Jurnal Sabilarrasyad, 2020)
Film is one of a mass communication media to deliver message easily and quickly to public through the audio-visual. In Indonesia, there are many films that raise the issue of social life within Indonesian society into big screen to provide information, entertainments, and education. A Film is derived from the work of scriptwriter or director, but it can also come from a book. The story of a book can be visualized into a film that contains adaptation of scenarios.The film which based on the true story and adapted to be retold certainly have an adjustment that will affect the narrative as a film-forming elements which relates with aspect of the story, characters, problems, times, locations, etc. One of the film that adapted from a book is the Sokola Rimba film based on the true story of Butet Manurung, a young women who fight to provides education for the isloated children in Bukit Dua Belas forest, Jambi.